Demobilization in British and French Africa at the End of the First World War. (January 2015) - Fogarty, Richard S.; Killingray, David
This article reconsiders important aspects of African participation in the First World War, both in Europe and in Africa itself, as part of the British and French empires. More specifically, it explores demobilization at the end of the war in comparison with that process in Europe, paying close attention to the particularities of the colonial context. The article argues that, although French and British Africa were integrated significantly into their metropole's war efforts between 1914 and 1918, the experience of demobilization in these colonies does not conform to George Mosse's 'brutalization' thesis, which has been so influential in understanding postwar events in parts of Europe. Africans who participated in the British and French war efforts did not emerge from their experiences to roil the political landscape with discontent and violence, even if the effects of the war were still important in many areas of the continent. Further, the story of demobilization in Africa demonstrates the importance of attending to the specific context of the colonial 'peripheries', even as we recognize the important links that connect them to the metropolitan 'centres'.